(untitled) (Journal of Laboratory Animal Science, 2024)
Microbiological quality control is undertaken to check the health status of laboratory animals. Pathogens infect the laboratory animals in various respiratory, digestive, central nervous systems, haematopoietic systems, dermal systems, etc. PCR detects pathogens with high sensitivity and specificity when compared to ELISA. Multiplex PCR can detect two or more pathogens at the same time. Multiplex PCR gives result based on the enzyme activity, bonding between the primer and DNA. In the present study, animal samples were analysed for the pathogen DNA at the molecular level to know the health status of laboratory animals. The respiratory pathogens Mycoplasma pulmonis and Sendai virus were detected simultaneously at 245, 340 bp, respectively. The digestive pathogens Salmonella typhimurium and Clostridium piliforme were detected simultaneously at 246, 196 bp, respectively. The animals were free from the specific respiratory and digestive pathogens. The multiplex PCR method is beneficial to detect the various pathogens in the laboratory rodents using the high throughput method.